Imaginário, cibercultura e cidadania a interferência do fenômeno glocal interativo na ressignificação da cidadania na contemporaneidade - Ferreira, Lygia Socorro Sousa (2019)
This thesis aims at studying the resignified citizenship – both in its exercise and conceptually speaking – by means of the interactive glocal phenomenon in its transpolitical dimension in the cyberculture, considering its social-historical context, also understood as a material and imaginary configuration, stemming from the many transformations originated in the technological communication sphere from the mid twentieth century on. In this context, characterized by continuous improvement in technology and science and also by the application of computing connected in the web, this interactivity possess absolute value, promoting a vertiginous growth of political and social mobilizations associated with web communities. The established relations in these media environments presuppose some level of decentralized power internally articulated, which move towards the needs of media exposure. Hence, this research main objective is to analyze this new concept of being/becoming a citizen, but now framed in web environments, acting strategically in terms of contradictions and expansions, exposure and retreat, in which there’s a subversion of modernity in the emergency as a language of endurance and struggle for status in the dromocratic cybercultural society. Having this in mind, it becomes advisable to investigate the impacts caused by this current resignification of citizenship, asking what transformations and practical contributions derives from these resignification phenomenon associated with this new model of web citizenship. As our hypothesis we have that this resignified citizenship made by the interactive glocal phenomenon collaborates for the rise of a new form of citizenship, whose imaginary participation, in real time, favors neonomadic citizens to get mobilized through social media, around issues related to civil rights that are going to be nourished in mobile interactive contexts, or outside them, not characterizing it as a strict obedience to the rules of the cybercultural system. This research relies on the thought of many authors: Bauman, Harvey, Jameson, Lyotard (post-modernity); Breton (communication utopia); Castoriadis (imaginary theory); Virilio (sociodromology); Trivinho (cyberculture, dromocracy and glocal phenomenon); Marshal and Carvalho (citizenship); and Foucault and Agamben (dispositive and panoptism). These concepts and trends are articulated through a critical analysis based on the phenomenical grasp of sociocultural and historical processes related to the current media civilization layout, emphasizing the questions concerning the subject – his/her condition – in the civilization. It is important to highlight that this thesis has also found its development in a reflexive analysis of posts, which were extracted from the social media (Facebook and Twitter), selected through hashtags, and concerning issues linked to citizen rights. This research aims at contributing to a critical approach to the cybercultural field study, based on the understanding that the glocal interactive phenomenon, in its transpolitical dimension, collaborates to resignify citizenship not only in the web environment, but also in daily life